2020
DOI: 10.3390/sym12071108
|View full text |Cite
|
Sign up to set email alerts
|

Racemic Phospholipids for Origin of Life Studies

Abstract: Although prebiotic condensations of glycerol, phosphate and fatty acids produce phospholipid esters with a racemic backbone, most experimental studies on vesicles intended as protocell models have been carried out by employing commercial enantiopure phospholipids. Current experimental research on realistic protocell models urgently requires racemic phospholipids and efficient synthetic routes for their production. Here we propose three synthetic pathways starting from glycerol or from racemic solketal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Racemic heterochiral membranes are comparably stable to homochiral membranes, demonstrating that LUCA could have had a stable heterochiral membrane. [4,6,27,32] Heterochiral membranes are defined here as having both R and S stereochemistries. The Yamagishi laboratory formed homochiral and heterochiral liposomes of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) and polar lipids isolated from Thermoplasma Ester and ether bonds of G3P and G1P, respectively, are highlighted in yellow.…”
Section: Heterochiral Vs Homochiral Membranes In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Racemic heterochiral membranes are comparably stable to homochiral membranes, demonstrating that LUCA could have had a stable heterochiral membrane. [4,6,27,32] Heterochiral membranes are defined here as having both R and S stereochemistries. The Yamagishi laboratory formed homochiral and heterochiral liposomes of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) and polar lipids isolated from Thermoplasma Ester and ether bonds of G3P and G1P, respectively, are highlighted in yellow.…”
Section: Heterochiral Vs Homochiral Membranes In Vitromentioning
confidence: 99%
“…[2] It has been theorized that lipid chirality must affect membrane stability and function. [3][4][5][6] In vitro techniques are invaluable to test the hypothesis that LUCA had a heterochiral membrane. Advances in genetic engineering have allowed recreation of heterogeneous LUCA-like membranes in model organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Crystals can be enantiomorphic in 100% [18], exacerbating more distinct properties than in case of racemic crystals. Heterochiral and homochiral membranes have significant distinct properties in packaging organization as in lipid rafts and in membrane permeability [1,15]. Phospholipids are aggregates organized as bilayer membranes [20].…”
Section: The "Advantage" To Be Homochiralmentioning
confidence: 99%
“…In addition, specific recognition of lipids with various ligands and lipid raft organization are essential properties to finely tune up enzymatic activities that are significantly different in homo and in hetero chiral membranes. However, recent investigations showed that homochirality packaging of phospholipids in prebiotic protocells [23] was not necessary a prerequisite, since it was sufficient to have compartment property of the heterochiral membranes [1]. For example, bilayers and vesicles composed of heterochiral lipids have a useful permeability, since these bilayers are looser than the more compact homochiral bilayers.…”
Section: The "Advantage" To Be Homochiralmentioning
confidence: 99%
See 1 more Smart Citation